Vicarious Liability dalam Pertanggungjawaban Perusahaan Otobus atas Kelalaian Sopir: Studi Kasus Putusan - Kennedy, Alexander (CV. Lenggogeni Data Publishing, 2025)
Abstract This article analyzes the application of vicarious liability in Indonesian civil law through Article 1367 of the Civil Code (KUHPer) as a derivation of Article 1365, using District Court of Sidoarjo Judgment No. 331/Pdt.G/2022/PN Sda as a case study. Using a normative juridical method and statutory, case, and conceptual approaches, the study underscores the “gatekeeping” role of the unlawful act (PMH) before liability can be attributed to the employer. To interpret the scope of employment, the article applies three practical lenses: control-benefit, functional integration, and foreseeability and proposes using criminal judgments as facts in civil proceedings. The novelty lies in turning principles into measurable evidentiary indicators (safety SOPs, fatigue management, telematics, operational documentation) to distinguish enterprise risk from personal negligence. The findings show the driver acted within the scope, making the bus company jointly liable; the framework improves predictability, strengthens victim protection, and promotes compliance by design. Keywords: Tort, Vicarious Liability, Private Law. Abstrak Artikel ini menganalisis penerapan vicarious liability dalam hukum perdata Indonesia melalui Pasal 1367 KUHPer sebagai derivasi Pasal 1365 KUHPer, dengan studi kasus Putusan PN Sidoarjo No. 331/Pdt.G/2022/PN Sda. Berbasis metode yuridis normatif dan pendekatan perundang-undangan, kasus, serta konseptual, penelitian menegaskan peran “gatekeeping” PMH sebelum atribusi tanggung jawab pada majikan. Untuk menafsirkan ruang lingkup pekerjaan, artikel menerapkan secara praktis tiga lensa: kontrol-manfaat, integrasi fungsional, dan keterkiraan risiko, serta mengusulkan pemanfaatan putusan pidana sebagai fakta di ranah perdata. Kebaruan terletak pada transformasi asas menjadi indikator pembuktian yang terukur (SOP keselamatan, manajemen kelelahan, telematika, dokumentasi operasional) guna membedakan risiko usaha dari kelalaian pribadi. Temuan menunjukkan tindakan sopir berada dalam jabatan sehingga PO bus bertanggung renteng; kerangka ini meningkatkan prediktabilitas putusan, memperkuat perlindungan korban, dan mendorong compliance by design.